Institutional pedagogical monitoring and quality of teaching performance in initial education institutions - Castañeda Estrada, Liliana Mercedes (2023)
The purpose of this research is to determine the relationship between institutional pedagogical monitoring and the quality of teaching performance in educational institutions. It is an investigation that corresponds to the Positivist paradigm, quantitative approach, basic type, descriptive level and correlational design. The population consisted of 60 initial education teachers. The survey technique was applied for both variables and as instruments two questionnaires, validated and reliable. The instrument that measures the variable: Institutional pedagogical monitoring presents a reliability index of .864 and the one that measures the variable Quality of teaching performance has an index of .788, measured with Cronbach's alpha. The results of the research report a statistically positive and significant relationship between institutional pedagogical monitoring and the quality of teaching performance, in a 95% confidence interval. Likewise, significant positive relationships were found between the pedagogical use of time, the use of pedagogical tools, the use of teaching materials and resources, and the management of the school climate with the quality of teaching performance.